Pengembangan Media Pembelajaran ‘Kenalin’ Berbasis Aplikasi Smart Apps Creator Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas IV Sekolah Dasar - Na'im Mushlihurrohman; Suratno (Postgraduate, University of Mataram, 2024)
Science and Technology learning in class IV at SD Negeri Kandri 01 is still not optimal in the use of IT-based learning media. This affects the learning outcomes of students who have not met the KKTP. This research aims to develop, and test the feasibility, and effectiveness of the